DETERMINING THE SPECIAL PHYSICAL FITNESS OF YOUNG BOXER GIRLS - Khadiyatullayev Ziyodulla Shukhratillayevych (Proximus Journal Publishing, 2024)
In this article, we will determine the special physical fitness, physical qualities, strength, speed, agility, flexibility, endurance, indicators of young girl boxers who are participating in the national boxing team of Uzbekistan.
Keywords: physical fitness; physical qualities; agility; strength